The Role of Frontal Cortical and Medial-Temporal Lobe Brain Areas in Learning a Bayesian Prior Belief on Reversals - Jang, Anthony I.; Costa, Vincent D.; Rudebeck, Peter H.; Chudasama, Yogita; Murray, Elisabeth A.; Averbeck, Bruno B. (The Journal of neuroscience, 2015)
Reversal learning has been extensively studied across species as a task that indexes the ability to flexibly make and reverse deterministic stimulus-reward associations. Although various brain lesions have been found to affect performance on this task, the behavioral processes affected by these lesions have not yet been determined. This task includes at least two kinds of learning. First, subjects have to learn and reverse stimulus-reward associations in each block of trials. Second, subjects become more proficient at reversing choice preferences as they experience more reversals. We have developed a Bayesian approach to separately characterize these two learning processes. Reversal of choice behavior within each block is driven by a combination of evidence that a reversal has occurred, and a prior belief in reversals that evolves with experience across blocks. We applied the approach to behavior obtained from 89 macaques, comprising 12 lesion groups and a control group. We found that animals from all of the groups reversed more quickly as they experienced more reversals, and correspondingly they updated their prior beliefs about reversals at the same rate. However, the initial values of the priors that the various groups of animals brought to the task differed significantly, and it was these initial priors that led to the differences in behavior. Thus, by taking a Bayesian approach we find that variability in reversal-learning performance attributable to different neural systems is primarily driven by different prior beliefs about reversals that each group brings to the task. The ability to use prior knowledge to adapt choice behavior is critical for flexible decision making. Reversal learning is often studied as a form of flexible decision making. However, prior studies have not identified which brain regions are important for the formation and use of prior beliefs to guide choice behavior. Here we develop a Bayesian approach that formally characterizes learning set as a concept, and we show that, in macaque monkeys, the amygdala and medial prefrontal cortex have a role in establishing an initial belief about the stability of the reward environment.